The disengaged teen : helping kids learn better, feel better, and live better - Anderson, Jenny, 1972-; Winthrop, Rebecca (Crown, 2025)
Adolescents are hardwired to explore and grow, but many are disengaged from school and learning. Simultaneously bored and overwhelmed, this apathy is feeding an alarming teen mental health crisis. As teenagers become more independent, parents may feel powerless to help. Journalist Jenny Anderson and education expert Rebecca Winthrop combine original research with stories of kids who transformed their relationship with learning to create a tool kit for supporting your kid's academic and emotional growth and success.